The evolutionary conservation of eukaryotic membrane-bound adenylyl cyclase isoforms - Schultz, Joachim E. (Frontiers in Pharmacology, 2022)
The nine membrane-delimited eukaryotic adenylyl cyclases are pseudoheterodimers with an identical domain order of seven (nine) distinct subdomains. Bioinformatics show that the protein evolved from a monomeric bacterial progenitor by gene duplication and fusion probably in a primordial eukaryotic cell around 1.5 billion years ago. Over a timespan of about 1 billion years, the first fusion product diverged into nine highly distinct pseudoheterodimeric isoforms. The evolutionary diversification ended approximately 0.5 billion years ago because the present isoforms are found in the living fossil coelacanth, a fish. Except for the two catalytic domains, C1 and C2, the mAC isoforms are fully diverged. Yet, within each isoform a high extent of conservation of respective subdomains is found. This applies to the C- and N-termini, a long linker region between the protein halves (C1b), two short cyclase-transducing-elements (CTE) and notably to the two hexahelical membrane domains TM1 and TM2. Except for the membrane anchor all subdomains were previously implicated in regulatory modalities. The bioinformatic results unequivocally indicate that the membrane anchors must possess an important regulatory function specifically tailored for each mAC isoform.